PERSEPSI KRISTEN TERHADAP KEHIDUPAN MODERN - Adenan Adenan (Studia Sosia Religia, 2020)
AbstractThe modernization movement brings the West to a new, more modern and high-tech life that can affect the world globally, not only in terms of material development, structure and infrastructure, but also changes in thinking methods, lifestyles, ways of dress, politics, economics to shift to the perspective and the view of people's life that seeps on the shifting of religious doctrine. The Christian religion represented by the church with the modern reform movement gave a very strong influence on Christianity itself, causing physical battles between the church and supporters of moderation. Which claimed many lives, such as the brutal arson, of thinkers and priests. Keywords: Christian, Modern, Perception.